The dynamics of marine craft : maneuvering and seakeeping - Lewandowski, Edward M. (Advanced series on ocean engineering ;, 2004)
This book presents a theoretical treatment, as well as a summary ofpractical methods of computation, of the forces and moments that acton marine craft. Its aim is to provide the tools necessary for theprediction or simulation of craft motions in calm water and inwaves. In addition to developing the required equations, the authorgives relations that permit at least approximate evaluation of thecoefficients so that useful results can be obtained. The approachbegins with the equations of motion for rigid bodies, relative tofixed- and moving-coordinate systems; then, the hydrodynamic forcesare exa.